CSF Protein Concentration Shows No Correlation With Brain Volume Measures - Wuschek, Alexander; Grahl, Sophia; Pongratz, Viola; Korn, Thomas; Kirschke, Jan; Zimmer, Claus; Hemmer, Bernhard; Mühlau, Mark (Frontiers in Neurology, 2019)
Background: CSF protein concentrations vary greatly among individuals. Accounting for brain volume may lower the variance and increase the diagnostic value of CSF protein concentrations. Objective: To determine the relation between CSF protein concentrations and brain volume. Methods: Brain volumes (total intracranial, gray matter, white matter volumes) derived from brain MRI and CSF protein concentrations (total protein, albumin, albumin CSF/serum ratio) of 29 control patients and 497 patients with clinically isolated syndrome or multiple sclerosis were studied. Finding: We found significant positive correlations of CSF protein concentrations with intracranial, gray matter, and white matter volumes. None of the correlations remained significant after correction for age and sex. Conclusion: Accounting for brain volume derived from brain MRI is unlikely to improve the diagnostic value of protein concentrations in CSF.